2022
DOI: 10.1002/adem.202200792
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm Activity of a Tunable Hypochlorous Acid‐Generating Electrochemical Bandage Controlled by a Wearable Potentiostat

Abstract: Chronic wound biofilm infections represent a major clinical challenge which results in a substantial burden to patients and healthcare systems. Treatment with topical antibiotics is oftentimes ineffective as a result of antibiotic‐resistant microorganisms and biofilm‐specific antibiotic tolerance. Use of biocides such as hypochlorous acid (HOCl) has gained increasing attention due to the lack of known resistance mechanisms. An HOCl‐generating electrochemical bandage (e‐bandage) is designed that delivers HOCl c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Previously, we used microelectrodes to show that these e-bandages produce HOCl at the working electrode, and that the HOCl can penetrate into biofilms and explant tissue. 15, 20 Here, free chlorine spectrophotometer test kits (TNT866; Hach Company, Ames, IA) were used to measure total HOCl content in wounds. Wounds harvested from mice treated with polarized e-bandages had higher levels of HOCl than those treated with non-polarized e-bandages (p = 0.170) or Tegaderm alone (p = 0.0045) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we used microelectrodes to show that these e-bandages produce HOCl at the working electrode, and that the HOCl can penetrate into biofilms and explant tissue. 15, 20 Here, free chlorine spectrophotometer test kits (TNT866; Hach Company, Ames, IA) were used to measure total HOCl content in wounds. Wounds harvested from mice treated with polarized e-bandages had higher levels of HOCl than those treated with non-polarized e-bandages (p = 0.170) or Tegaderm alone (p = 0.0045) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous results with e-bandages that produce an alternative reactive oxygen species, hydrogen peroxide (H2O2), found that wound healing was not only unimpeded but augmented, 20 however, antimicrobial efficacy of electrochemically generated H2O2 was less than HOCl against a broad spectrum of microorganisms. 12,22,[27][28][29][30] Therefore, a programmable e-bandage that can produce both HOCl and H2O2 for optimal biocide and wound healing augmentation respectively should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilms (initial, control, and e-bandage treated) were quantified by calculating CFUs as described previously (24, 28, 29). Briefly, e-bandages were removed from TSA plates and placed in Petri dishes.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, our group developed H 2 O 2 and (separately) HOCl-generating electrochemical bandages (e-bandages) consisting of carbon fabric working and counter electrodes (CEs) and a silver-silver chloride (Ag/AgCl) pseudo reference electrode to treat biofilms (24, 25). The electrodes were saturated with a phosphate buffered saline (PBS) based hydrogel and separated by layers of cotton fabric.…”
Section: Introductionmentioning
confidence: 99%